Self-esteem and its relationship to job satisfaction A field study on a sample of male and female teachers in Damascus - عربي كاتبي, محمد عزت; سليطين, فادي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the study was to find out the relationship between Self-esteem and job satisfaction among a sample of teachers in Damascus. And whether there are fundamentally significant differences in the averages of Self-esteem scores and job satisfaction depending on the variables of gender and teaching experience. The study sample consisted of (220) male and female teachers, including (85) male and (135) female teachers. The measurement tools were Al-Zuabi's Self-Esteem Scale (2013), and also used the scale of job satisfaction prepared by Abdul-Jawad and Metwally (1993). Validity and reliability of both tools were concluded. The results revealed that there are relatively middle levels in both Self-Esteem and job satisfaction among the sample members. Also, there was a positive relationship at the level of significance (0.01) between Self-Esteem and job satisfaction. Whereas, there were no statistically significant differences between the mean scores of Self-Esteem and job satisfaction among the members of the research sample due to the variables of sex and teaching experience.